Agricultura familiar no limite de uma estação ecológica: conflitos e cooperação na construção da sustentabilidade - Werneck, Laert Guerra (2017)
The integral sustainability promotion is prescribed in the law of the National System of conservation units of nature (SNUC) – but without tools to monitor its evolution, the managing around Units lacks information for its planning. This law determines “the effective participation of local populations in the creation, implementation and management of protected areas”. That happened in the case of the State ecological station of GuaxindibaEEEG, RJ, who had its Advisory Council installed after the creation and dissemination of management plan of the station. The investigation of the perceptions and opinions of actors – stakeholders – represented in the Council of this station allows the identification of points of conflict and the selection of indicators for the promotion of sustainability. Among these actors, the farmers are fundamental because they represent most people residing in the unit and have greater connection with the rural surroundings. A experimental research, qualitative, semi-structured interviews, questionnaires and field observations, seeks to propose indicators of sustainability of family agriculture for its monitoring. Using a proposed roadmap on MESMIS methodology with adaptations of the indicators suggested by the IBGE, this work has identified critical points for sustainability to compose a system with 18 indicators and its sub-indicators/variables totaling, a numeric index, applied to a qualitative scale, can result in eight levels of integral sustainability of family agriculture. This system was adapted for use in smartphones in a free application access with possibility of adjustment of some variables to other contexts. In terms of the difficulties raised, hydric resources management, the marketing and the misuse of pesticides can be faced with the incentive for the adoption of ecological production models.